Discovery of novel inhibitors targeting Plasmodium knowlesi dihydrofolate reductase using molecular docking and molecular dynamics simulation. (December 2021) - Yadav, Manoj Kumar; Tripathi, Manish Kumar; Yadav, Srishti
Abstract: Plasmodium knowlesi, recognized as the fifth Plasmodium parasite, is the least studied malaria parasite. It is a significant cause of morbidity and mortality in the South-East Asia region. Enzymes of folate synthesis, especially dihydrofolate reductase (DHFR), is a well-approved drug target in other Plasmodium species, but its role in Plasmodium knowlesi is poorly studied. This work characterizes Pk DHFR as a drug target and identifies inhibitors that can withstand the upcoming problem of resistance. The 3D structure of the Pk DHFR target is modelled using comparative modelling, and further, it is refined and validated using energy minimization and torsional angle analysis methods. We extracted 13 compounds from DrugBank and ZINC databases using the "target similarity search" criteria. These compounds were categorized based on their binding affinity (−4.49 to −10.08 kcal/mol) and pose prediction against the active site of Pk DHFR. Later on, the top 5 Pk DHFR–compound complexes with high or equivalent binding affinity to its natural ligand (dihydrofolate) have undergone for dynamics. The simulation experiments reveal the higher stability of DB00563- Pk DHFR complex and less conformational fluctuations and share a similar degree of compactness throughout the simulation trajectory. The MM/GBSA calculation of free energy of DB00563 is also the least (−72.84 kcal/mol) compared to others. Furthermore, the flexible side chain of DB00563 can bind and block the active site of Pk DHFR more efficiently. Thus, the identified drug may be considered as a potential candidate for treating P. knowlesi malaria. Highlights: Modelling of P. knowlesi DHFR-TS and used as a drug target to design inhibitors. Model quality evaluation and structural characterization of modelled protein. Screening of DrugBank and ZINC databases using "target similarity search" criteria against the modelled protein. Molecular docking and molecular dynamics simulation were used to identify the lead molecules and stability behaviour in the docked complexes. DB00563 due to its flexible side chain may able to efficiently block the Pk DHFR activity.